Contractualism as an element of democratic pedagogy? - Budde, Jürgen; Hellberg, Lotta; Weuster, Nora (JSSE - Journal of Social Science Education, 2022)
Pedagogical practices are based on establishing commitment. Contractual pedagogy corresponds to a contract-based social order. Contractual pedagogy aims at democratizing pedagogical relationships. Contractual pedagogy involves a pedagogic process of collective subjectivation. Contractual pedagogy does not represent the kind of pedagogical ‘counter-model’ familiar to progressive pedagogies that aspire towards democratic codetermination. Purpose: This article investigates the establishment of commitment in pedagogical practices through what are known as ‘behavioural contracts’. Such contracts are seen as a participatory element of democratic pedagogy and are linked to the aim of strengthening students’ self-determination. The objective is to demonstrate that as a pedagogical phenomenon, contractual pedagogy is oriented towards a practice of self-control achieved through external control, assuming a basis of sovereignty and reason. Methodology: The article provides an investigation of material from an ethnographic research project in Germany on social learning in school-based pedagogical contexts. The study is informed by practice theory, theory of school and theory of social pedagogics. Findings: This article argues that contractual pedagogy as a subjectivising constellation is primarily directed towards re-establishing the pre-existing institutional order. It demonstrates that contractual pedagogy can neither be understood as a particularly participatory method of democratic pedagogy, nor as a governmental power strategy, but as a subjectivising exercise that introduces students to a central tenet in modern societies. Through this, connections are formed between specific forms of (collective) subjectivation. Research implications: Further theoretical and empirical analyses are required, which make other pedagogical impulses, such as an ethics of care or the critique of the subject, fruitful for Democratic Pedagogy.